English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-06-30 08:45:17 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

81x^4 - 1 = (9x^2 + 1) (9x^2 - 1)

= (9x^2 + 1) (3x + 1) (3x - 1)

2007-06-30 08:48:11 · answer #1 · answered by Swamy 7 · 0 0

useful formula
a^2 - b^2 = (a+b) * (a-b)

81x^4 - 1 =
=(9x^2)^2 - (1)^2
= (9x^2 +1) * (9x^2 -1)

now
9x^2 - 1 =
= (3x)^ - (1)^2
= (3x +1 ) * (3x -1)
so,

= (9x^2 +1) * (9x^2 -1)
= (9x^2 + 1) * (3x +1) * (3x -1)

2007-06-30 08:56:21 · answer #2 · answered by buoisang 4 · 0 0

(3x-1)(3x+1)(9x^2 +1)

2007-06-30 08:58:05 · answer #3 · answered by ? 5 · 0 0

(9x^2-1)(9x^2+1)

2007-06-30 08:57:31 · answer #4 · answered by Dave aka Spider Monkey 7 · 0 0

fedest.com, questions and answers